PENINGKATAN KUALITAS PELAYANAN PUBLIK DI KANTOR DESA KAMBITIN BERDASARKAN PADA ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK (AAUPB) DALAM HUKUM ADMINISTRASI NEGARA - Cut Valisa (Jurnal PubBis, 2023)
ABSTRACT  In an effort to improve the quality of public services at the Kambitin Village office based on one the principles contained in the general principles of good governance (AAUPB) in state administration law, the village government, in this case the village apparatus, must also be able to realize the performance of public services in accordance with what is expected by the community. The purpose of this research is to identify and analyze the efforts of the village government in improving the quality of public services, along with identifying whether the Village Officials at the Kambitin Village Office have understood the importance of the general principles of good governance (AAUPB) in providing public services to village communities. Types and approaches using qualitative research are carried out by collecting words or sentences from individuals, books, and other sources. therefore, this qualitative research uses interview technique namely 5 (five) informants as a method of data collection. Data analysis techniques use interactive models (Miles & Huberman). The results of the study show that the performance of the village government in the delivery of public services has been carried out properly and is in accordance with the applicable laws and regulations. However, regarding the implementation of a community satisfaction survey for services at the Kambitin Village office, a community satisfaction survey has never been carried out either by village officials or from related survey agencies or institutions. The implications of this study indicate that efforts to improve the quality of public services have a very important role in order to achieve the goal of better service quality.